Female choice and annual reproductive success favour less-ornamented male house sparrows - Griffith, S. C. (1999)
Theories of sexual selection usually assume that female preferences for male ornamental traits are fixed and always likely to favour the largest or most extravagant sexual ornaments. This is not, however, always necessary or likely, particularly in resource-based monogamous systems. Here we show that in a closed population of house sparrows, small-badged males were preferred by females as both social and genetic mates and produced a higher number of viable offspring. Previous studies of other house sparrow populations have shown females to prefer large-badged males. Given the likely trade-offs operating between different male behavioural and morphological traits, we propose that female choice is a flexible adaptive strategy through which females can select those males likely to supply the male-acquired benefits that are locally most important.